Government spending composition in a simple model of Schumpeterian growth - Simon Wiederhold (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
This paper investigates the relevance of government purchasing behavior for innovation-based economic growth. We construct a parsimonious Schumpeterian growth model in which demand from the public sphere can effectively alter the economy's rate of technological change. We incorporate results of various empirical studies arguing that public sector demand acts as incentive for private innovation activities. In contrast to the standard Schumpeterian growth framework, we account for industry heterogeneity in terms of innovation potential. This extension allows to bring government demand policy within the realm of the growth policy debate. By varying the composition of its purchases, the government can induce a reallocation of private resources to stimulate the rate of technological change. This comes along with temporarily faster economic growth. Moreover, our welfare analysis implies that it is always worth implementing a policy in which industries benefit from public purchases subject to their specific innovation size.
Keywords: E62; H54; H57; O31; O32; O41; 330; public demand; endogenous technological change; Schumpeterian growth; Öffentliche Beschaffung; Innovation; Endogener technischer Fortschritt; Schumpeterismus; Neue Wachstumstheorie; Theorie